Factors associated with registrant availability for unrelated adult donor hematopoietic stem cell donation: Analysis of the stem cell registry at Canadian Blood Services. Issue 1 (21st October 2020) - Monaghan, Madeline; Yi, Qi‐Long; Green, Meagan; Campbell, Todd; Weiss, Jason T.; Dibdin, Nicholas; Mercer, Dena; Elmoazzen, Heidi; Allan, David S.
Abstract: Background: Greater use of unrelated donors to support hematopoietic cell transplantation can be hampered by unavailability of registrants when identified as potential candidates for donation. Methods: Multivariate analysis was performed to identify donor factors associated with availability for verification of human leukocyte antigen typing (VT) needed before donor activation. All VT requests for registrants on the Canadian Blood Services Stem Cell Registry between 1 January and 31 December 2018 were reviewed (n = 1358). Results: Potential donors identified by transplant centers were categorized as available at the time of VT but ineligible for medical or other reasons (n = 130 and excluded from further analysis), available (n = 622) or unavailable (n = 566) due to scheduling, loss of interest, and/or inability to contact. With multivariate analysis, registrants who previously donated blood, those recruited online or from blood donation clinics, and a shorter interval between registration and VT request were significantly correlated with increased donor availability. Donor sex and geographic location, however, displayed no correlation. Conclusion: Online registration and recruitment at whole blood donation centers should be enhanced to increase the availability of registrants at VT. More insight is needed to maintain registrant availability following community in‐person recruitment events, especially if the interval between registration and activation is prolonged. Recruitment of male registrants who are well informed should not negatively impact availability.